Blocking of associative learning by explicit descriptions - Kelly, Tom; Ludvig, Elliot A. (Cognition, 2025)
People given written descriptions often learn and decide differently from those learning from experience, even in formally identical tasks. This paper presents two experiments detailing how telling participants about the value of one stimulus impacts a keystone learning effect – blocking. The paper investigates if descriptions can be used to effectively block future trial-by-trial learning. Participants were presented with coloured shape stimuli and asked if those shapes caused reward. Experiment 1 found both standard, trial-by-trial experienced blocking and the novel effect of described blocking of future trial-by-trial learning. Experiment 2 investigated the conditions that promote described blocking by manipulating the training that occurred prior to exposure to the description. In the Pre-training Present group, participants exposed to a training set of compound and elemental stimuli produced more pronounced blocking than the Pre-training Absent group, which had no such training. These results show that explicit descriptions about causal relations can block learning from subsequent experience, providing a new extension of associative learning toward the verbal domain.